Variety of Political Expressions: Study of Khilafatism Discourse on Islamic Salafi Websites in Indonesia - M Mujibuddin; M Fakhru Riza (Al Qalam, 2022)
This study aims to analyze the ideology of khilafat discourse on Salafi websites in Indonesia. The presence of the Salafi group is not singular. Salafi groups develop according to the situation. In Indonesia, there are three Salafi groups: Salafi purists, Salafi haraki, and Salafi jihadi. All three also have websites devoted to the da'wah wing and produce discourses according to their respective ideologies. This research is qualitative, and data collection is done using observation and netnography. The objects of this research include three websites, namely muslim.or.id, majelismujahidin.com, and ansyarusyariah.com. The results of this study indicate that the website muslim.or.id represents the salafy purist group because it is a-political. The proof is that the article on this website emphasizes obedience to the legitimate leader even though it does not apply Islamic law as a whole. Meanwhile, the website Majelismujahidin.com represents haraki (political) groups who want to establish an Islamic state in Indonesia. Finally, the website ansyarusyariah.com represents the salafy jihadi group that wants to select an Islamic state and make jihad the primary way to fight for an Islamic state.